Prevention of Initial Depressive Disorders Among at-Risk Portuguese Adolescents. Issue 4 (July 2019) - Matos, A. Paula; Pinheiro, M. do Rosário; Costa, José J.; do Céu Salvador, M.; Arnarson, Eiríkur Ö.; Craighead, W. Edward
Abstract: This study evaluated whether Arnarson and Craighead's (2009, 2011) developmentally based behavioral and cognitive program that prevented the initial episode of depressive disorders among Icelandic adolescents could be adapted to prevent depressive disorders among "at-risk" Portuguese adolescents. One hundred sixty-eight Portuguese mid-adolescents (primarily 14 to 15 years old), who had subsyndromal symptoms of depression but who had never met criteria for a depressive disorder, were identified by classroom screening with the CDI and subsequent K-SADS-PL interview. All 168 adolescents were offered participation in the 14-week prevention program; 70 agreed to participate in the program, and 98 agreed to participate only in an assessment control group. Psychological disorders were evaluated at baseline, 6-, 12-, 18-, and 24-month assessments. During the 2-year follow-up period, 12 students in the assessment-only group experienced an initial depressive disorder versus 2 in the prevention group. Survival analyses indicated a significantly lower rate of initial episodes of depressive disorders, χ 2 (1) = 4.261, p = .039, among the prevention group participants compared to the assessment only comparison group. The hazard ratio was .207, and the NNT was 11. Survival analyses indicated no significant differences between the prevention condition and the assessment only condition in the occurrence of other psychiatric disorders, χ 2(1) = 1.080, p = .299. The findings indicate the program can be successfully adapted for use in Portuguese schools, and they provide a preliminary indication that those "at-risk" adolescents who chose to participate in the program, compared to those who chose to participate only in the assessments, developed fewer initial episodes of depressive disorders over the course of 24 months. The program effects were similar to the outcomes of the prior study of this program in Iceland. As in the Icelandic version of the program, its effects appeared to be specific to the depressive disorders for which the program was designed. Highlights: Mood disorders have a rapid rate of onset of first episodes during ages 15-18 We evaluated a developmentally- and school-based CBT "indicated" program " At risk" Portuguese adolescents volunteered for the 14-week program Program participants had significantly fewer episodes than a control group Program effects (HR -.207) were sustained for 24 months of treatment and follow-up